The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/10755470211011166
|View full text |Cite
|
Sign up to set email alerts
|

Foregrounding Backgrounds: How Scientists Conceive Art to Express the Invisible

Abstract: Scientist-artist collaborations have become a high-profile form of science communication as scientists seek creative ways to connect with publics. This qualitative case study examines one such collaboration from the perspective of scientist and artist participants’ experiences with the purpose and meaning of art. To do so, we draw on John Dewey’s concept of art as experience and Nigel Thrift and other nonrepresentational theorists’ emphasis on overlooked backgrounds that suffuse daily life. We find that sci-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In addition, our research identified a range of external goals, many of which align with those found in prior research, including goals to reveal overlooked beauty [Parks & White, 2021] and to critique and problematize [Catts & Zurr, 2018].…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…In addition, our research identified a range of external goals, many of which align with those found in prior research, including goals to reveal overlooked beauty [Parks & White, 2021] and to critique and problematize [Catts & Zurr, 2018].…”
Section: Discussionsupporting
confidence: 63%
“…A subset of creators also expressed clear science communication goals, such as teaching or sharing scientific facts and making science more accessible [Burns et al, 2003], in line with some previous research into SciArt goals [Collver & Weitkamp, 2018;Parks & White, 2021]. Others shared goals that have traditionally been conceptualized as science communication-related, such as raising awareness, sparking dialogue, inspiring audiences, or encouraging participation [Kappel & Holmen, 2019;Metcalfe, 2019].…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations